2011
DOI: 10.5455/vetworld.2011.429-432
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Relation to Diseases and Heat stress in Poultry

Abstract: Different diseases conditions and stress factors are responsible for high morbidity and mortality of present day poultry. Nutritional strategy and proper feed formulation with specific dietary regimen can combat this up to a certain extent. The incidence of various infectious diseases, nervous disorders and metabolic disorders can be minimized through proper feed regimen. There is a stiff competition and restrictions in the global market of poultry products which can be addressed with proper management of emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 1 publication
1
7
0
2
Order By: Relevance
“…The present results are in agreement with those reported by Kirunda et al (2001), Bollengier-Lee et al (1998) and Das et al (2011), who showed that the addition of vit. E could reduce the negative impact of high ambient temperature on performance of laying hens and blood plasma parameters.…”
Section: Al-harthisupporting
confidence: 83%
“…The present results are in agreement with those reported by Kirunda et al (2001), Bollengier-Lee et al (1998) and Das et al (2011), who showed that the addition of vit. E could reduce the negative impact of high ambient temperature on performance of laying hens and blood plasma parameters.…”
Section: Al-harthisupporting
confidence: 83%
“…Various stresses may increase energy demands for immune regulation at the expense of energy reserves, and then reduce the energy available for growth and other processes [ 59 , 60 ]. Furthermore, disease and nutrition are closely interlinked [ 61 ]. The immune variations under ambient pressures may trigger energy metabolic changes in mollusks [ 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daily feed intake, egg mass, and egg production in laying hens were significantly reduced by chronic heat stress (Mignon-Grasteau et al, 2015). The increased temperature decreases energy requirement and feed intake but requirements for protein, minerals, and vitamins do not decrease, therefore the biological mechanism by which heat stress impacts production performance is partly explained by reduced feed intake (Das et al, 2011). The results of the present study provide initial evidence of the biological mechanisms through which the reduced production performance is probably due to the reduced feed intake when laying ducks were exposed to high ambient temperature.…”
Section: Discussionmentioning
confidence: 99%